The genomics of mimicry: Gene expression throughout development provides insights into convergent and divergent phenotypes in a Müllerian mimicry system. Issue 16 (16th July 2021) - Stuckert, Adam M. M.; Chouteau, Mathieu; McClure, Melanie; LaPolice, Troy M.; Linderoth, Tyler; Nielsen, Rasmus; Summers, Kyle; MacManes, Matthew D.
Abstract: A common goal in evolutionary biology is to discern the mechanisms that produce the astounding diversity of morphologies seen across the tree of life. Aposematic species, those with a conspicuous phenotype coupled with some form of defence, are excellent models to understand the link between vivid colour pattern variations, the natural selection shaping it, and the underlying genetic mechanisms underpinning this variation. Mimicry systems in which multiple species share the same conspicuous phenotype can provide an even better model for understanding the mechanisms of colour production in aposematic species, especially if comimics have divergent evolutionary histories. Here we investigate the genetic mechanisms by which vivid colour and pattern are produced in a Müllerian mimicry complex of poison frogs. We did this by first assembling a high‐quality de novo genome assembly for the mimic poison frog Ranitomeya imitator . This assembled genome is 6.8 Gbp in size, with a contig N50 of 300 Kbp R .  imitator and two colour morphs from both Ranitomeya fantastica and R .  variabilis which R .  imitator mimics. We identified a large number of pigmentation and patterning genes that are differentially expressed throughout development, many of them related to melanocyte development, melanin synthesis, iridophore development and guanine synthesis. Polytypic differences within species may be the result of differences in expression and/or timing of expression, whereas convergence for colour pattern between species does not appear to be due to the same changes in gene expression. In addition, we identify the pteridine synthesis pathway (including genes such as qdpr and xdh ) as a key driver of the variation in colour between morphs of these species. Finally, we hypothesize that genes in the keratin family are important for producing different structural colours within these frogs.